Systemic Inflammatory Response Index as a Predictor of Postoperative Infectious Complications in Elderly Patients Undergoing Posterior Spinal Instrumentation - Agar, Anil; Key, Sefa; Yavuz, Hamza (Mdpi, 2025)
Objective: To assess the predictive value of systemic inflammatory markers for postoperative complications in older adults undergoing posterior spinal instrumentation for either lumbar spinal stenosis (LSS) or osteoporotic vertebral fractures (OVFs). This study design as a retrospective observational study. Methods: Fifty-four patients aged >= 55 years who underwent posterior spinal instrumentation between 2020 and 2023 were retrospectively analyzed. Patients were grouped into LSS (n = 27) and OVF (n = 27) cohorts. Preoperative, early postoperative, and 6-month follow-up systemic inflammatory marker levels, including the Systemic Inflammatory Response Index (SIRI), Systemic Immune-Inflammation Index (SII), Neutrophil-to-Lymphocyte Ratio (NLR), Platelet-to-Lymphocyte Ratio (PLR), and Monocyte-to-Lymphocyte Ratio (MLR), were recorded. The primary outcome was the occurrence of postoperative infectious complications. ROC curve analysis was conducted to evaluate the discriminatory power of each marker. Results: SIRI values were significantly higher in the OVF group than in the LSS group at all time points (p < 0.05). Postoperative complications occurred in 7.4% of patients, equally distributed between groups. ROC analysis showed that preoperative SIRI had the highest predictive value (AUC = 0.743), with a cutoff value of 2.69 yielding 100% sensitivity and 65.3% specificity. Other indices showed poor predictive accuracy (AUC < 0.70). Conclusions: Preoperative SIRI is a promising, easily obtainable biomarker for identifying older patients at higher risk of postoperative complications following posterior spinal instrumentation. Its implementation may improve preoperative risk stratification in spine surgery.
Keywords: systemic inflammatory response index (SIRI); osteoporotic vertebral fracture (OVF); lumbar spinal stenosis (LSS); posterior instrumentation; spine surgery; inflammation; elderly patients